Guide to Ancient Near Eastern Art - Ezra, Ruth; Harris, Beth; Zucker, Steven (Open textbook library., 2019)
This book contains all of Smarthistory’s content for Sumerian, Akkadian, Neo-Sumerian / Ur III, Babylonian, Assyrian and Persian art.